Optimization of power conversion efficiency of polyvinyl-alcohol/titanium dioxide compact layer using response surface methodology/central composite design - Mustafa, Muhammad Norhaffis; Shafie, Suhaidi; Wahid, Mohd Haniff; Sulaiman, Yusran (Elsevier, 2019)
In this study, response surface methodology by central composite design (RSM/CCD) was used as an efficient approach for modeling and optimizing titanium dioxide (TiO2) as a compact layer via electrospinning for dye-sensitized solar cell (DSSC) performances. The concentration of polyvinyl alcohol (PVA) and volume of titanium isopropoxide (TTIP) were investigated by RSM/CCD and the interaction between these factors was studied and modeled to identify the significant parameters toward DSSC performance. The statistical analysis showed that these two factors have significantly affected the power conversion efficiency (PCE). The model obtained was valid and capable to predict the response model accurately as the model was able to obtain the coefficient of determination (R2) of 0.9958 with below 5% residual standard error.